Left ventricular segmental strain based on speckle tracking echocardiography versus indications of immune inflammation in patients after COVID-19 pneumonia - Nikita E. Shirokov; Elena I. Yaroslavskaya; Dmitry V. Krinochkin; Nadezhda A. Osokina; Natalia A. Musikhina; Tatyana I. Petelina (Russian Open Medical Journal)
Background — The significance of cytokine activation and immune inflammation in subclinical damage to cardiomyocytes and resulting development of the congestive heart failure (CHF) is frequently discussed in published studies, as well as whether there are cardiac lesions in COVID-19 survivors identified by the speckle tracking echocardiography (STE). Objective — To examine the association of echocardiographic parameters with indications of immune inflammation in patients recovered from COVID-19 pneumonia depending on segmental longitudinal strain (LS) of the left ventricle (LV) identified by STE. Methods — Our study encompassed 216 patients (51.1% men, mean age of 50.1±11.1 years) distributed among two groups: Group I (n=108) included study subjects with segmental LS (≥3 LV segments) revealed by the STE; Group II (n=108) comprised patients without visually detectable LV lesions. All patients were examined three months after COVID-19 pneumonia. Results — Groups did not differ statistically significantly in terms of LV ejection fraction (68.7±4.3% in Group I vs. 68.6±4.3% in Group II; p=0.916). Global LS was significantly lower in the Group I than in the Group II at the time of the control follow-up visit three months later (-18.2 [-16.7; -19.4] % vs. -20.6 [-19.5; -22.1] %, respectively; p<0.001). When analyzing laboratory indications of immune inflammation in groups, we revealed statistically significantly higher values in Group I vs. Group II in the concentrations of interleukin 6 (3.1 [2.4;3.9] pg/mL vs. 2.5 [3.8;4.7] pg/mL; p=0.009), C-reactive protein (4.7 [2.9;8.3] mg/L vs. 3.0 [1.5; 5.3] mg/L; p<0.001), and tumor necrosis factor α (6.0 [4.8;4.1] pg/ml vs. 5.0 [4.0;6.4] pg/ml; p=0.001). In Group I, we detected diffuse lesion of LS (≥4 segments of the same LV level; 38.0% of patients) and regional lesion of LS (≥3 segments corresponding to the blood supply pools of the anterior, circumflex, or right coronary arteries; 62.0% of patients). According to logistic regression, the LS of the basal LV level (OR 3.028; 95% CI 1.909-4.802; р<0.001) in combination with LS of the apical LV level (OR 1.287; 95% CI 1.099-1.507; р=0.002) and LV lateral wall annular velocity assessed by tissue Doppler imaging, peak e’ (OR 0.774; 95% CI 0.657-0.911; р=0.002) had an independent relationship with each of diffuse and regional LS lesions. Conclusion — Based on STE data, we have identified a relationship of diffuse and regional LV lesions with features of systolic and diastolic LV dysfunction and markers of immune inflammation in patients three months after COVID-19 pneumonia.